Nutrition in the prevention and treatment of disease - Coulston, Ann M., ....-; Boushey, Carol J., ....- (Amsterdam : Elsevier, 2008)
Expertly edited, the Second Edition of Nutrition in the Prevention and Treatment of Disease offers 18 completely new chapters and 50% overall material updated. Given its unique focus and extensive coverage of clinical applications and disease prevention, this edition is organized for easy integration into advanced upper-division or graduate nutrition curriculums. Foundation chapters on nutrition research methodology and application clearly link the contributions of basic science to applied nutrition research and, in turn, to research-based patient care guidelines. Readers will learn to integrate basic principles and concepts across disciplines and areas of research and practice as well as how to apply this knowledge in new creative ways. Chapters on specific nutrients and health cover topics where data are just beginning to be identified, such as choline, antioxidants, nutrition and cognition, and eye disease. Established areas of chronic disease: obesity, diabetes, cardiovascular disease
Gastrointestinal disease, and bone health are presented each in their own sections, which aim to demonstrate the inter-action of basic science, genetics, applied nutrition research, and research-based patient care guidelines. No other nutrition book on the market takes this approach. Students will take away foundational insights into the application of nutrition research in the prevention and treatment of disease. Busy researchers and clinicians will use this book as a "referesher course" and should feel confident in making patient care recommendations based on solid current research findings. * 18 completely new chapters and 50% overall new material * Unique focus and extensive coverage of clinical applications and disease prevention. * Clearly links the contributions of basic science to applied nutrition research and, in turn, to research-based patient care guidelines. * Assimilates a large body of research and applications and serves as a "refresher course" for busy researchers and clinicians.
Keywords: Voeding; Ziektepreventie